Effects of CH3OH Addition on Plasma Electrolytic Oxidation of AZ31 Magnesium Alloys*supported by National Natural Science Foundation of China (No. 21376088), the Project of Production, Education and Research, Guangdong Province and Ministry of Education (Nos. 2012B09100063, 2012A090300015), and Guangzhou Science and Technology Plan Projects of China (No. 2014Y2-00042). (September 2015) - He, Yongyi; Chen, Li; Yan, Zongcheng; Zhang, Yalei
Abstract Plasma electrolytic oxidation (PEO) films on AZ31 magnesium alloys were prepared in alkaline silicate electrolytes (base electrolyte) with the addition of different volume concentrations of CH3OH, which was used to adjust the thickness of the vapor sheath. The compositions, morphologies, and thicknesses of ceramic layers formed with different CH3OH concentrations were determined via X-ray diffraction (XRD), energy-dispersive spectroscopy (EDS), and scanning electron microscopy (SEM). Corrosion behavior of the oxide films was evaluated in 3.5 wt.% NaCl solution using potentiodynamic polarization tests. PEO coatings mainly comprised Mg, MgO, and Mg2SiO4. The addition of CH3OH in base electrolytes affected the thickness, pores diameter, and Mg2SiO4 content in the films. The films formed in the electrolyte containing 12% CH3OH exhibited the highest thickness. The coatings formed in the electrolyte containing different concentrations of CH3OH exhibited similar corrosion resistance. The energy consumption of PEO markedly decreased upon the addition of CH3OH to the electrolytes. The result is helpful for energy saving in the PEO process.